Optimizing Optimalisasi Ketersediaan Produk-produk Pertanian Berbasis Organic Farming Menuju Gaya Hidup Sehat melalui Sistem Pertanian Terpadu - Syamsul Hadi; Muhammad Hazmi; Insan Wijaya; Arief Noor Akhmadi; Muhammad Iwan Wahyudi (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
A crucial problem faced by the target village community is the inhibition of changing the paradigm of the farmer community on the process of changing the mindset and action patterns in organic and conventional cultivation systems. In fact, the potential for the application of organic farming in the village is wide open, because the market for organic fertilizers and biological pesticides has started to run. The objective of the IbDM program is to optimize the supply of organic-based agricultural products towards healthy living. The implementation method used to find solutions to problems is in the form of social engineering and technological engineering approaches through socialization and training. The approach taken to the engineering process is in the form of a participatory approach, empowerment, and inter-entrepreneurial development in an effort to strengthen the capacity of community human resources by involving stakeholders through the village system model. The results of program implementation are as follows: 1) Socialization of the IbDM program with the results of partners understanding intellectually about the concept of this activity and are ready to participate in building an organic village; 2) The organic village cycle has been implemented properly with the formation of the Organic Farming Institute (OFI)) Al-Istiqomah; 3) Soil sample analysis has been carried out with 10 types of complete analysis and a 3 hectare demonstration plot mapping has been carried out; 4) A comparative study has been carried out to Gapoktan Al-Barokah Bondowoso; 5) Training has been carried out on the manufacture of organic materials; and 6) The results of the participatory review showed the achievement of success indicators of 65% and OFI performance of 30.23% or semi empowered and ready to go organic.